Identification of a Novel Hemizygous SQSTM1 Nonsense Mutation in Atypical Behavioral Variant Frontotemporal Dementia - Sun, Lin; Rong, Zhouyi; Li, Wei; Zheng, Honghua; Xiao, Shifu; Li, Xia (Frontiers in Aging Neuroscience, 2018)
Frontotemporal dementia includes a large spectrum of neurodegenerative disorders. SQSTM1, coding for p62 protein, plays a vital role in the pathogenesis of FTD. Here, we report a case of a female patient with SQSTM1 mutation S224X, who was 59 years old when she initially exhibited memory decline, mild personality changes, and subtle atrophy of frontal/temporal lobes in magnetic resonance imaging (MRI). Genetic testing revealed a nonsense mutation of the SQSTM1 gene (S224X), resulting in premature termination of protein synthesis and a predicted truncated protein 217 amino acids shorter than the normal protein. Moreover, neither intact nor truncated SQSTM1 proteins was detectable in SQSTM1 S224X mutant overexpressing HEK-293T cells. We assayed for SQSTM1 cDNA in samples from the patient’s peripheral leucocytes, and did not detect its mutation. The test of quantitative PCR showed significant decreased level of SQSTM1 mRNA from peripheral leucocytes of the patient compared to five dementia controls. Our results identify a novel pathogenic SQSTM1 S224X mutation in an atypical FTD patient accompanied with loss of SQSTM1/p62 protein expression probably due to SQSTM1 gene haploinsufficiency.